2021
DOI: 10.3390/plants10020221
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Plant Na+-P-Type ATPases: From Saline Environments to Land Colonization

Abstract: Soil salinity is one of the major factors obstructing the growth and development of agricultural crops. Eukaryotes have two main transport systems involved in active Na+ removal: cation/H+ antiporters and Na+-P-type ATPases. Key transport proteins, Na+/K+-P-ATPases, are widely distributed among the different taxa families of pumps which are responsible for keeping cytosolic Na+ concentrations below toxic levels. Na+/K+-P-ATPases are considered to be absent in flowering plants. The data presented here are a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…To maintain K + /Na + homeostasis in the cytoplasm under salt stress, plants limit the accumulation of Na + and the loss of K + ( Hussain et al., 2021 ). Eukaryotes have two major Na + efflux systems: the salt overly sensitive (SOS) system, which is a universally conserved salt tolerance pathway in plants; and the Na + /K + -ATPase system in bacteria, fungi, moss, and mammals ( Nakayama et al., 2010 ; Jacobs et al., 2011 ; Dabravolski and Isayenkov, 2021 ). The function of SOS1 relies on the plasma membrane (PM)-localized H + -ATPase that hydrolyzes adenosine triphosphate (ATP) to generate energy and pumps H + out of the cytoplasm to generate an electrochemical gradient ( Qiu et al., 2002 ; Haruta and Sussman, 2012 ; Yang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain K + /Na + homeostasis in the cytoplasm under salt stress, plants limit the accumulation of Na + and the loss of K + ( Hussain et al., 2021 ). Eukaryotes have two major Na + efflux systems: the salt overly sensitive (SOS) system, which is a universally conserved salt tolerance pathway in plants; and the Na + /K + -ATPase system in bacteria, fungi, moss, and mammals ( Nakayama et al., 2010 ; Jacobs et al., 2011 ; Dabravolski and Isayenkov, 2021 ). The function of SOS1 relies on the plasma membrane (PM)-localized H + -ATPase that hydrolyzes adenosine triphosphate (ATP) to generate energy and pumps H + out of the cytoplasm to generate an electrochemical gradient ( Qiu et al., 2002 ; Haruta and Sussman, 2012 ; Yang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an evolutionary context, Na + /K + -ATPases can be divided into animal and fungal types, flowering plants are generally considered to lack Na + /K + -ATPases ( Pedersen et al., 2012 ; Dabravolski and Isayenkov, 2021 ). Genomic analyses revealed that genes encoding Na + /K + -ATPases were lost during evolution and land settlement, suggesting that Na + /K + -ATPases might exist in eukaryotes living in high-salinity marine environments ( Garciadeblas et al., 2001 ; Pedersen et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%